The Effectiveness of Ball Throwing and Catching Games: Analysis of Basic Manipulative Movement Skills in Elementary School Students - Aditya, Revi; Kriswanto, Erwin Setyo; Pambudi, Aris Fajar; Yuliarto, Hari; Munir, Ali (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
Basic manipulative movements are an important skill in the motor development of elementary school children, particularly in throwing and catching a ball. However, the limited variety of physical education instruction has resulted in students’ manipulative skills not developing optimally. Therefore, active, enjoyable learning methods tailored to students’ characteristics are needed, one of which is the game of catch. This study aims to determine the effect of ball-throwing and catching games on improving basic manipulative motor skills in fourth-grade students at State Elementary School 1 Kalisari Natar, South Lampung. This study uses a quantitative approach with a pre-experimental one-group pretest-posttest design. The population in this study consisted of 25 students. The sampling method used was total sampling, resulting in a sample size of 25 subjects for this study. The instruments in this study involved a basic manipulative movement test before (pretest) and after the treatment (posttest) with a 4-week intervention. The data analysis techniques included the Shapiro–Wilk normality test and hypothesis testing using the paired-samples t-test. The results showed that there was a significant effect of ball throw-and-catch games on improving students' basic manipulative movement skills, with a calculated t-value of 3.9192, which is higher than the table t-value of 2.0639 at a significance level of α = 0.05, t (24) = 3.919, p < 0.001, Cohen’s dz = 0.78. Therefore, ball throw-and-catch games are effective to use in physical education learning to improve elementary school students' basic manipulative movement skills.